Simulation-Based Multi-Objective Optimization For Distributed Material Transportation System - Mohamad, Nor Rashidah; Md Fauadi, Muhammad Hafidz Fazli; Jafar, Fairul Azni; Mohamed Noor, Ahamad Zaki; Nordin, Mohd Hisham (Science Publishing Corporation, 2018)
Material Transportation System (MTS) is required to move materials within a factory, warehouse, or other facilities. This study focused on AGV where the optimization of MTS is further studied. Although there is increasing demand in AGV control architecture, there is still unexplored potential in optimizing AGV performance measures. Applying AGVs in logistic factory may help in improving the efficiency in material flow and distribution among workstation at the right time and the right place. The aim of this study is to propose a simulation-based vehicle requirement analysis of AGVs in warehouse area with low mixed product variation. Simulations results show optimized number of AGV in warehouse area is achieved and succeed in produce short cycle time with high throughput.